1999
DOI: 10.1002/(sici)1521-3765(19990604)5:6<1905::aid-chem1905>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Desymmetrization ofmeso-cis-1,2-Cyclohexanedimethanol with Differentiation between Diastereotopic and Enantiotopic C−H Bonds by (−)-Sparteine-Mediated Deprotonation

Abstract: The deprotonation of a dicarbamate prepared from cis-1,2-cyclohexanedimethanol by sec-butyllithium/(À)-sparteine proceeds with efficient selection between the enantiotopic branches and their diastereotopic protons with high preference for the pro-S proton at the R branch to afford the intermediate, configurationally stable lithium compound as a single diastereomer. Trapping of this intermediate by electrophiles (DOMe, CO 2 , CH 3 I, Me 3 SiCl, or R 3 SnCl) takes place with retention of the configuration to yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The reaction of (S)-8 via 10 with methyl iodide, chlorotrimethylsilane, chlorotributyltin, and acetone also yielded the expected compounds 14 with high diastereoselectivity (for spectroscopic data, see Table 3). As we had already observed in related cases, 12 no stereospecifity with respect to the former carbanionic center was achieved in the reaction with allyl bromide (Table 1, Entry 11). In all other cases, deprotonation and substitution -as found for all sp 3carbamoyloxy-substituted carbanions -proceeded with complete stereoretention.…”
Section: Methodssupporting
confidence: 60%
“…The reaction of (S)-8 via 10 with methyl iodide, chlorotrimethylsilane, chlorotributyltin, and acetone also yielded the expected compounds 14 with high diastereoselectivity (for spectroscopic data, see Table 3). As we had already observed in related cases, 12 no stereospecifity with respect to the former carbanionic center was achieved in the reaction with allyl bromide (Table 1, Entry 11). In all other cases, deprotonation and substitution -as found for all sp 3carbamoyloxy-substituted carbanions -proceeded with complete stereoretention.…”
Section: Methodssupporting
confidence: 60%
“…A spectacular development in this field was achieved by Hoppe et al, who demonstrated that the complex s BuLi/ (−)-sparteine could induce the enantioselective deprotonation of achiral alkyl carbamates. , The chiral lithium species thus formed can be alkylated with retention of configuration to give the protected secondary alcohols in high ee’s. The use of these lithium species has so far been limited as a result of their configurational lability above −70 °C, although Hoppe and others have reported various applications of this methodology.…”
mentioning
confidence: 99%
“…Thus, the whole transmetallation/alkylation process occurred with retention of the configuration [20]. The treatment of the trimethyl-or tributylstannanes 25 with nbutyllithium at low temperature generated the corresponding organolithium intermediates with high yields and purities, as estimated from the trapping experiments with some electrophiles, obtaining the corresponding products 26 with diastereomeric ratios of 99:1 and >95% of enantiomeric excess (Scheme 5) [21].…”
Section: Transmetallation: Tin/lithium Exchangementioning
confidence: 88%